2021
DOI: 10.3389/fpls.2021.667493
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping and Validation of Loci for Kernel-Related Traits in Wheat (Triticum aestivum L.)

Abstract: Kernel size (KS) and kernel weight play a key role in wheat yield. Phenotypic data from six environments and a Wheat55K single-nucleotide polymorphism array–based constructed genetic linkage map from a recombinant inbred line population derived from the cross between the wheat line 20828 and the line SY95-71 were used to identify quantitative trait locus (QTL) for kernel length (KL), kernel width (KW), kernel thickness (KT), thousand-kernel weight (TKW), kernel length–width ratio (LWR), KS, and factor form den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 82 publications
5
18
0
Order By: Relevance
“…These studies revealed the potential for pleiotropism of corresponding traits and also revealed the genetic correlations among SD, SL, and SNS. In addition, higher SD may result in shorter kernels and smaller TKW, being consistent with the study reported by Qu et al (2021) . Thus, it is essential to determine relationships among different characters to accelerate breeding process.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These studies revealed the potential for pleiotropism of corresponding traits and also revealed the genetic correlations among SD, SL, and SNS. In addition, higher SD may result in shorter kernels and smaller TKW, being consistent with the study reported by Qu et al (2021) . Thus, it is essential to determine relationships among different characters to accelerate breeding process.…”
Section: Discussionsupporting
confidence: 91%
“…In the CS genome, the QSd.sicau-2D.3 identified by Liu et al (2019) overlapped with QSd.sau-2SY-2D between 605.12 and 609.88 Mb on chromosome 2DL ( Figure 3A ); qSc-7A ( Fan et al, 2019 ), explaining 4.87–17.22% of variation in SD, was located between 679.70 and 679.92 Mb, and QSd.sau-2SY-7A.2 was mapped to between 678.47 and 682.29 Mb ( Figure 3B ), indicating that they may be allelic variants. In addition, comparing with the physical maps of QTL for other yield-related traits such as SNS ( Ding et al, 2021 ), KL, KW, kernel thickness (KT), TKW, kernel length–width ratio (LWR), and kernel size (KS) ( Qu et al, 2021 ), none of the physical regions of QTL for SD in the present study overlapped with these yield-related loci.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thousand Grain Weight is a key determinant that is related to grain yield potential in wheat and is influenced by both genetic and environmental factors ( Wang L. et al, 2012 ; Avni et al, 2018 ; Duan et al, 2020 ). Compared with other yield components, TGW had more stable phenotypic variation and higher heritability ( Mir et al, 2012 ; Wang L. et al, 2012 ; Cheng et al, 2015 ; Hu et al, 2015 ; Krishnappa et al, 2017 ; Avni et al, 2018 ; Kumari et al, 2018 ; Duan et al, 2020 ; Xin et al, 2020 ; Yang et al, 2020 ; Gao et al, 2021 ; Qu et al, 2021 ). Likewise, TGW trait in the present study also showed a prominent main-effect of genotype, with a high heritability ( h 2 B = 0.77), relatively lower CV% (6.08-12.80%), and significant correlations ( r = 0.62 ** −0.92 ** ) in the performance of the RILs under eight different environments.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to identify major TGW quantitative trait loci (QTL) and further exploit elite genes in the genetic improvement of modern wheat breeding programs. In the last two decades, a large number of QTLs underlying TGW have been successfully identified by traditional bi-parental linkage mapping ( Cheng et al, 2015 ; Hu et al, 2015 ; Krishnappa et al, 2017 ; Kumari et al, 2018 ; Xin et al, 2020 ; Qu et al, 2021 ) and genome-wide association approaches ( Mir et al, 2012 ; Yang et al, 2020 ; Gao et al, 2021 ). These loci provide a great convenience for revealing the genetic basis of wheat TGW formation.…”
Section: Introductionmentioning
confidence: 99%